Identification of Character Impact Odorants of Wood Apple Fruit (Feronia Limonia) - Anton Apriyantono; Bakti Kumara (Jurnal Teknologi dan Industri Pangan, 2004)
The volatiles of the kawista fruit (wood apple) were analyzed by gas chromatography (GC) and a combined gas chromatography-mass spectrometer (GC-MS). Character impact odorants of the fruits were systematically characterized by aroma extract dilution analysis (AEDA) with GC-Olfactometry (GC-O). A total of 75 compounds were identified, including 28 esters, 11 alcohols, 10 aldehydes, 1 acetal, 10 ketones, 4 lactones, 1 heterocyclic, 4 aliphatic hydrocarbons, 1 furan and 5 acids. However, only 44 volatiles were detected by GC-O. Among these, compounds with the most impact were ethyl butyrate (fruity, sweet, banan-like)and methyl butyrate (fruit, sour) with a flavor dilution factor of 256 and 64, respectively. Based on AEDA results, butyric acid, 3-mathyl valeric acid, 1-octen-3-ol, pentyl isobutyrate, 2-ethyl hexanoic acid, ethyl octanoate, gamma-decalactone, 2,3-pentanedione, 3-octanone, 5-methyl-3-heptanone, 9-methyl-5-undecene and (E)-2-hexenyl butyrate seem to contribute to kawista fruit flavor. Key words : Character impact compounds, GC-MS, GC-Olfactometry, AEDA, Feronia limonia